Ensino de biologia por investigação no contexto das doenças cardiovasculares na Educação de Jovens e Adultos - Santos, Monique Cesnik Martins dos (2020)
The educational guidelines for Youth and Adult Education (EJA) signal the identity of this type of teaching and point to the need for a specific pedagogical model that is consistent with the profile of students and their life paths. The curriculum must be flexible and consider meaningful content for young people and adults. The approach should promote motivation and provide adequate mediation for students to actively participate in the teaching and learning process. The literature shows a contextualized and investigative approach, generating significant and transformative learning. Reflecting on these conceptions and in search of a pedagogical proposal aimed at EJA students, it is that this work presents Cardiovascular Diseases. This theme, combined with teaching by research, is proposed as a way to support and contextualize the teaching of Biology, providing meaningful content, in dialogue with the experiences and interests of students. Thus, the present work seeks to analyze the contribution of an investigative approach, contextualized, interdisciplinary and integrated with the didactic unit of human physiology for the teaching of Biology in Youth and Adult Education (EJA). The target audience are students from the VI cycle of EJA from a school in the state of Paraíba, located in the capital. The methodological approach is qualitative and descriptive as to the nature of the data, collected through structured questionnaires and participant observation. Pre-test questionnaires were applied in order to verify the students' perceptions regarding their own level of knowledge and / or difficulties in the listed themes. These initial data supported the direction of the investigative didactic sequence, in addition to being a comparative parameter after the activities. After the execution of the proposal, post-test questionnaires were applied in order to raise the relevance of the didactic sequence produced. The results pointed to the effectiveness of the investigative and contextualized strategy adopted. The contextualized theme, exposure to the school community, group work, the investigative approach and the articulation of different languages and other subjects, were factors that demonstrated positive effects on learning, favoring the integration of contents and interdisciplinarity. Students demonstrated motivation, leadership and autonomy in the construction of knowledge. They positively evaluated the proposed theme and the methodological approach used. They revealed, through their perceptions and attitudes, the development of significant learning and the potential to multiply the knowledge built by acting as health promoters and transformers of their reality. This process proved to be effective in bringing to the student the feeling of belonging to the school, of school and social insertion. Students felt valued individually and collectively as an EJA modality. The product from this work is presented in a didactic manual format, with a detailed description of the activities. Thus, this pedagogical experience can be shared, serving as a contribution to teachers interested in the investigative approach and / or who work in teaching and learning in Biology at EJA.